2022
DOI: 10.1002/er.7955
|View full text |Cite
|
Sign up to set email alerts
|

Layered double hydroxide composite membrane for advanced alkaline water electrolysis

Abstract: Summary The development of alkaline membranes with high conductivity and stability is a significant challenge for the commercial application of advanced alkaline water electrolysis. In this study, a novel anion exchange membrane (AEM) was fabricated by quaternary ammonium poly (n‐methyl‐piperidine‐co‐p‐terphenyl) (QAPPT) and Ni‐Fe layered double hydroxide (LDH) synthesis for advanced alkaline water electrolysis. The uniform dispersion of Ni‐Fe LDH in the QAPPT/Ni‐Fe LDH composite membrane was confirmed by scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…For example, Lv et al reported a quaternary ammonium poly (n-methylpiperidine-co-p-terphenyl) (QAPPT)/FeNi LDH composite PA-AEM. 189 The authors found that the QAPPT AEM with a low doping content of 3 wt% achieved a significantly higher hydroxide conductivity of 217.6 mS cm À1 compared with that (B130 mS cm À1 ) of the pristine QAPPT AEM. The 1 M KOH-fed AEMWE with a QAPPT/3% FeNi LDH AEM achieved 1 A cm À2 at 1.82 V. The cross-linking strategy has been used to address the trade-off between hydroxide conductivity and stability of PA-AEMs.…”
Section: 332mentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Lv et al reported a quaternary ammonium poly (n-methylpiperidine-co-p-terphenyl) (QAPPT)/FeNi LDH composite PA-AEM. 189 The authors found that the QAPPT AEM with a low doping content of 3 wt% achieved a significantly higher hydroxide conductivity of 217.6 mS cm À1 compared with that (B130 mS cm À1 ) of the pristine QAPPT AEM. The 1 M KOH-fed AEMWE with a QAPPT/3% FeNi LDH AEM achieved 1 A cm À2 at 1.82 V. The cross-linking strategy has been used to address the trade-off between hydroxide conductivity and stability of PA-AEMs.…”
Section: 332mentioning
confidence: 98%
“…At present, the commercial Zirfon PERL composite membrane has been successfully used in alkaline liquid water electrolysis, which consists of hydrophilic ZrO 2 nanoparticles (85 wt%) and a polysulfone backbone with an average pore size of 150 nm. There are two regions in the porous Zirfon PERL membrane: (1) interconnected ZrO 2 pores (B30 nm); 165 2, 164 3, 166 4, 167 5, 168 6, 163 7, 169 8, 170 9, 39 10 151 , 11, 171 12, 172 13, 19 14, 173 15, 174 16, 69 17, 175 18, 176 19, 51 20, 177 21, 178 22, 179 23, 26 24, 180 25, 181 26, 182 27, 183 28, 67 29, 184 30, 185 31, 186 32, 74 33, 187 34, 29 35, 46 36, 36 37, 188 38, 189 39, 190 40, 54 41, 191 42, 192 43, 27 44, 47 45, 34 46, 193 47, 76 48, 49 49, 68…”
Section: Hydroxide Ion Conductive Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…20−22 In the case of HER catalysts on photocathodes, where fewer studies have been reported, RuO 2 23 or even Pt have been used to achieve record efficiencies for solar driven water splitting. 24 Bifunctional NiFeP catalysts 25 and layered double hydroxides (LDH), 26 originally developed for other applications, e.g., electrolysis 27 and degradation of organic pollutants, 28 could also find their place as catalysts in photoelectrodes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…FeOOH and NiOOH have been proposed as inexpensive OER catalysts for otherwise unstable BiVO 4 photoanodes, while CoPi has been used extensively for improving the charge transfer efficiency of metal oxide photoanodes. In the case of HER catalysts on photocathodes, where fewer studies have been reported, RuO 2 or even Pt have been used to achieve record efficiencies for solar driven water splitting . Bifunctional NiFeP catalysts and layered double hydroxides (LDH), originally developed for other applications, e.g., electrolysis and degradation of organic pollutants, could also find their place as catalysts in photoelectrodes.…”
Section: Introductionmentioning
confidence: 99%